Results of instrumental aerial survey of ice-associated seals on the ice in the Okhotsk Sea in May 2013 - Vladimir I. Chernook; Aleksey I. Grachev; Alexandr N. Vasiliev; Irina S. Trukhanova; Vladimir N. Burkanov; Boris A. Solovyev (Известия ТИНРО)
Populations of ice-associated seals in the Okhotsk Sea are assessed using modern instrumental aerial technique. The aerial survey was conducted over a part of the ice-covered area of the Sea on May 1-9, 2013 by means of thermal scan and visual digital photography from the aircraft-laboratory An-38 «Vostok». The ice covered area of the Okhotsk Sea in the time of survey was estimated as 242,000 km2, and 2,993 km2 of it was covered by survey transects with total length 5,617 km. The number of animals on all transects within the equipment swath was counted. Four seal species were identified: bearded, spotted, ribbon, and ringed seals, and their number and distribution were determined. The infra-red scanner recorded 5,730 seals on the ice and 4,360 these animals were photographed including 844 ringed seals, 453 bearded, 721 spotted, 1,805 ribbon, 435 pups non-identified to the species, and 102 non-identified to species adult seals. These assessments were extrapolated over the whole ice-covered area of the Okhotsk Sea using a linear model framework, and the following estimations of the species total abundance were presented (95 % confidence intervals in brackets): 88,253 (64,120-130,320) ringed seals, 39,743 (27,868-60,026) bearded seals, 181,179 (118,392-316,995) ribbon seals, and 84,356 (55,172-113,540) spotted seals. A database on all recorded seals with their «portrait-photos» and accompanying information is created on materials of the aerial survey. The developed instrumental technology can be used as a basis for wider aerial surveys of ice-associated seals in the North Pacific.